Dadru Kusta Under the Lens of Ayurveda (International Journal of Ayurveda and Pharma Research, 2025)
The skin is considered as largest organ in our body, it maintains the body temperature, stores water, fat, vit D. In Ayurveda skin diseases considered mainly under the spectrum of Kusta, the meaning of which is that causes disfiguration. As it is Tridoshaja vyadhi but type of Kustha depends upon predominance of particular Dosha (biological energies). The Acharyas including Charaka, Sushruta, Vagbhata divided Twak vikara into two, Maha kusta and Kshudra kusta. The Dadru kusta is one among them and commonly compared to fungal infections based on the appearance. Certain occupations increase the risk of these infections from the environment like extreme summer, rainy seasons and repeated contacts from infected person with use of personal belongings has high chances of causing infections. Here is a case study of male 32-year-old having Dadru symptoms and for this we have planned Nitya virechana (regular therapeutic purgation) and Shaman chikitsa (oral medications).